Adenosine is released during thalamic oscillations to provide negative feedback control. (15th September 2022) - Wall, Mark J.; Puddefoot, Katie; Yin, Wencheng; Bingham, Chris; Seifi, Mohsen; Swinny, Jerome D.; Ngomba, Richard Teke
Abstract: Physiological oscillations in the cortico-thalamo-cortical loop occur during processes such as sleep, but these can become dysfunctional in pathological conditions such as absence epilepsy. The purine neuromodulator adenosine can act as an endogenous anticonvulsant: it is released into the extracellular space during convulsive seizures to activate A1 receptors suppressing on-going activity and delaying the occurrence of the next seizure. However, the role of adenosine in thalamic physiological and epileptiform oscillations is less clear. Here we have combined immunohistochemistry, electrophysiology, and fixed potential amperometry (FPA) biosensor measurements to characterise the release and actions of adenosine in thalamic oscillations measured in rodent slices. In the thalamus, A1 receptors are highly expressed particularly in the ventral basal (VB) thalamus and reticular thalamic nucleus (nRT) supporting a role for adenosine signalling in controlling oscillations. In agreement with previous studies, both adenosine and adenosine A1 receptor agonists inhibited thalamic oscillations in control (spindle-like) and in epileptic conditions. Here we have shown for the first time that both control and epileptiform oscillations are enhanced (i.e., increased number of oscillatory cycles) by blocking A1 receptors consistent with adenosine release occurring during oscillations. Although increases in extracellular adenosine could not be directly detected during control oscillations, clear increases in adenosine concentration could be detected with a biosensor during epileptiform oscillation activity. Thus, adenosine is released during thalamic oscillations and acts via A1 receptors to feedback and reduce thalamic oscillatory activity. Highlights: Thalamus oscillations occur in sleep and are enhanced in pathological conditions. We have investigated the role of adenosine in thalamic oscillations. We have combined electrophysiology, biosensor recording and immunohistochemistry. There is dense A1 receptors expression in the nRT. Adenosine modulates both non-epileptiform and epileptiform thalamic oscillations.